PENGARUH JKT48 SEBAGAI BRAND AMBASSADOR ERIGO APPAREL TERHADAP KEPUTUSAN PEMBELIAN - Putra, Arifin -; Megawati, Liya (Jurnal Ilmiah Wahana Pendidikan, 2024)
Today the trend of online shopping (Online Shopping) continues to grow rapidly, so that many parties are trying to take advantage of this opportunity as a place to sell products. Erigo Apparel is a local Indonesian fashion brand that competes with business people in other fashion sectors through online stores and social media. As one of the marketing strategies implemented, Erigo Apparel cooperates with the idol group JKT48 from Jakarta Indonesia, which is the sister group of the famous AKB48 idol group from Akihabara Japan which has millions of fans and JKT48 has been around for more than 12 years since its inception. This study aims to prove the influence of JKT48 as Erigo Apparel's brand ambassador on purchasing decisions. The sample used in this study are fans of the JKT48 idol group who are more than 15 years old. The analytical technique used is the Multiple Linear Regression technique, so that it can be easier to see whether JKT48 has an effect on the decision to buy Erigo Apparel products.